Identification of Active Surface Species in Molten Carbonates Using in situ Raman Spectroscopy - Zhang, Peng; Wu, Tao; Huang, Kevin (Frontiers in Energy Research, 2021)
Here we report the results of a study on active surface species of a pristine and modified (Li-Na)2CO3 eutectic using in situ Raman spectroscopy technique. The effects of gas compositions, temperature, time and alkaline earth have been systematically studied. The species of CO42-, HCO4- and C2O52- are identified as the three major active species on the surface of (Li-Na)2CO3 eutectic by a combined Raman spectroscopy and theoretical density functional theory (DFT) calculations. The results further reveal that CO42-, HCO4- and C2O52- are preferably formed in the presence of O2, H2O, and high CO2 concentration. With the addition of Ba to the pristine (Li-Na)2CO3 eutectic, the Raman CO42-/HCO4- shifts become more pronounced.